Lonely Planet's beautiful world (Lonely Planet, 2013)
Journey to the planets most magnificent places with Lonely Planet's Beautiful World, a thought provoking portrait of our world. This lavishly produced hardback will help you see the planet as you have never seen it before, renewing your relationship with the place we call home.